The Pentatricopeptide Repeat Protein EMB2654 Is Essential for Trans-Splicing of a Chloroplast Small Ribosomal Subunit Transcript. Issue 2 (23rd December 2016) - Aryamanesh, Nader; Ruwe, Hannes; Sanglard, Lilian Vincis Pereira; Eshraghi, Leila; Bussell, John D.; Howell, Katharine A.; Small, Ian; des Francs-Small, Catherine Colas
Abstract : Binding of the pentatricopeptide repeat protein EMB2654 to one-half of the plastid rps12 intron is essential for trans-splicing, production of plastid ribosomes, and embryogenesis in Arabidopsis. Abstract: We report the partial complementation and subsequent comparative molecular analysis of two nonviable mutants impaired in chloroplast translation, one ( emb2394 ) lacking the RPL6 protein, and the other ( emb2654 ) carrying a mutation in a gene encoding a P-class pentatricopeptide repeat protein. We show that EMB2654 is required for the trans-splicing of the plastid rps12 transcript and that therefore the emb2654 mutant lacks Rps12 protein and fails to assemble the small subunit of the plastid ribosome, explaining the loss of plastid translation and consequent embryo-lethal phenotype. Predictions of the EMB2654 binding site match a small RNA "footprint" located on the 5′ half of the trans-spliced intron that is almost absent in the partially complemented mutant. EMB2654 binds sequence specifically to this target sequence in vitro. Altered patterns in nuclease-protected small RNA fragments in emb2654 show that EMB2654 binding must be an early step in, or prior to, the formation of a large protein-RNA complex covering the free ends of the two rps12 intron halves.